Modification, Fabrication and Performance Evaluation of Insulated Box for Post-Harvest Handling of Fish - Atanda, S. A.; Anifowoshe, A. O.; Oladeinde, M. O.; Olumoh, Q. A.; Udefi , I. O.; Pessu, P. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
In order to address the challenges associated with postharvest handling of fresh fish, Nigerian Stored Products Research Institute (NSPRI) developed an insulated transportation mechanism named Ice Fish Box™ which has a capacity of 18 kg of fish and ice. However, capacity and ease of movement was encountered in the developed box leading to modification using a smaller box (inner box) of dimension 495 mm×340 mm× 340 mm fitted into a bigger box of dimension 540 mm×360 mm× 360 mm and a trolley on wheels using human muscle power for ease of movement. The construction was carried out using standard procedures and all materials used were sourced locally. Results of its performance tests indicated that the modified box can carry approximately 60 kg of fish and ice at full load and the trolley can carry load of up to 120 kg of stacked boxes and swerves easily at angle 45º. It is expected that these modifications would allow for more storage of fish and ease movement on all terrains as handlers mostly women find it almost difficult in moving the earlier designed insulated box around.